Pengaruh Store Image, Store Atmospherics, dan Store Theatrics Terhadap Keputusan Pembelian pada Kedai Amarta Semarang - Leni Purnita Sari; Sri Suryoko; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
The development of more modern area make a change for trend or lifestyle in society. Modern society who came in to restaurant or cafe is not only for enjoying the food and drink, but also to enjoying the atmosphere who created by the cafe. this makes business people in culinary business should consider store environment at his cafe or restaurant.Creativity restaurant in creating attractive store environment would be added value. Store environment created by the restaurant to be one factor in encouraging of purchase decision. The store environment included store image, store atmospherics, and store theatrics. T This research was conducted as the sales at Kedai Amarta Semarang continued to fluctuate from 2010-2013, so we have to know store image, store atmospherics, and store theatrics influence the purchase decision.The purpose of this study is to find out the influence of store image, store atmospherics, and store theatrics to the purchasing decision at Kedai Amarta Semarang. The type of researh is explanatory research. Interviews with questionnaire were adopted for data collection in this study. Hundred people were employed as respondent by purposive sampling technique. The respondents were visitors Kedai Amarta Semarang who have made a purchase of at least two times.The research results showed that store image, store atmospherics, store theatrics influenced on purchase decisions, partially or simultaneously. The results obtained by analyzing the primary data with validity test, reliability test, crosstab analysis, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and a significance test (t and F) using SPSS for Windows version 15,0.Based on the results, the researcher suggests that Kedai Amarta management need to improve service, maintain the quality of food and drink , increase the variety of the menu, increase the variety of types of music played, increase the availability of the parking area, change the decor theme appropriate the present moment, and update the program promotion.